Addressing the needs of women affected by armed conflict : an ICRC guidance document - Lindsey-Curtet, Charlotte; Holst-Roness, Florence Tercier; Anderson, Letitia; International Committee of the Red Cross (Geneva : ICRC, 2004)
The aim of this guidance document is to provide a working tool to ensure the provision of appropriate programmes and services to and with women affected by armed conflict. It is targeted to ICRC policy-makers, field staff and international organizations concerned with the planning, funding and implementation of humanitarian programmes for women. The document also presents an overview of the relevant legal framework of humanitarian law, human rights law and refugee law specific to women in situations of armed conflict. It is divided into two parts. Part 1 discusses violations of human rights when the distinction between civilians and combatants gets blurred in conflict situations. Part 2 highlights the specific needs of women deprived of their freedom and offers tools for more effective and appropriate responses.
"International Committee of the Red Cross, Women and War."
Includes bibliographical references (pages 161-166).
Keywords: Women and war; War victims; War -- Protection of civilians; Women -- Crimes against; GUIDELINES; HEALTH; INTERNATIONAL HUMANITARIAN LAW; MANUALS; WOMEN